The Recitation of Imam Abu Mujliz Al-Sudusi (d. circa 101 AH) A Compilation and Analytical Study - Majeed, Muhammad Omar (Journal of Islamic Sciences, 2025)
This study aims to collect and document the Qur’anic readings attributed to Imam Abū Mijlaz Lāḥiq ibn Ḥumayd al-Sadūsī (d. ca. 101 AH), a prominent figure of the Basran school in Qur’anic exegesis and qirāʾāt. The research systematically traces these readings from primary classical sources, organizes them according to the order of the Qur’anic surahs, and provides precise source citations, while highlighting the differences between his readings and the widely accepted canonical readings. The study deliberately refrains from engaging in syntactic, semantic, or phonetic analysis.The central issue addressed by this research lies in the absence of a comprehensive and dedicated academic work that compiles all of Abū Mijlaz’s recorded readings in one place with accurate referencing, unlike previous studies which treated his readings within broader exegetical, phonological, or grammatical contexts. The methodology adopted is based on inductive collection and textual documentation, following the approach of early scholars such as Ibn Mujāhid and Abū ʿAmr al-Dānī, who reported variant readings without interpretive commentary.Among the key findings of this research is the documentation of over 76 distinct readings attributed to Abū Mijlaz. This constitutes a significant contribution to the field of Qur’anic variant readings, filling a scholarly gap by preserving the textual legacy of one of the notable successors (tābiʿūn). The work serves as a well-structured and reliable reference for researchers concerned with non-canonical qirāʾāt and the historical development of Qur’anic recitation.
Keywords: Canonical readings; non-canonical readings; Abū Mijlaz; Al-Sadūsī; Basran school